2019
DOI: 10.1039/c9cc03579f
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the performance of germanium nanowire anodes for Li-ion batteries by direct growth on textured copper

Abstract: Capacity retention of directly grown Ge nanowire anodes is enhanced by replacing stainless steel with textured Cu foil current collectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…[ 2,4,8,9,15–18 ] However, even as these CCs offer various advantages, they present a number of challenges. For example, the low surface area of planar metal foils is not ideal for achieving the much needed high Si NW loading, [ 9,19 ] and often results in low yields (e.g., 0.18–0.4 mg cm −2 ). [ 1,2,4,9,18,20 ] The electrical and mechanical properties of carbon based‐substrates are also inferior.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,4,8,9,15–18 ] However, even as these CCs offer various advantages, they present a number of challenges. For example, the low surface area of planar metal foils is not ideal for achieving the much needed high Si NW loading, [ 9,19 ] and often results in low yields (e.g., 0.18–0.4 mg cm −2 ). [ 1,2,4,9,18,20 ] The electrical and mechanical properties of carbon based‐substrates are also inferior.…”
Section: Introductionmentioning
confidence: 99%
“…[99][100][101][102][103] The stable capacity behavior observed for Si/CuSi coincided with the formation of a robust interconnected framework of nanometer-sized Si ligaments, capable of overcoming stressinduced fracturing of the SEI layer upon repeated expansion and contraction of the active material. [1,2,62,68,[108][109][110] SEM of Si/CuSi (1.24 mg cm −2 ) after 5 and 50 cycles (Figure 6a,b) allowed the evolution of the crystalline Si NWs to an amorphous Si mesh to be tracked. After 5 cycles, the wire-like morphology is still apparent with slight texturing and fusion of adjacent NWs (Figure 6a).…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with previous works that have suggested that the formation of this interwoven architecture is due to a combination of pore formation and electrochemical welding over successive cycles. [31,108,109,[111][112][113] The Si mesh layer demonstrates excellent adhesion to the underlying 3D CuSi NW framework. The Si mesh remains well anchored to both the bulk CuSi film and individual CuSi NWs after 300 cycles, with this behavior reflected by the electrochemical stability of Si/CuSi of different Si loadings (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, one-dimensional (1D) nanostructures have become the subject of extensive research, owing to their unique and excellent electrical, optical, thermal, mechanical, and magnetic properties. To date, many literature studies have reported the potential applications of 1D nanostructures in new nanoelectronic devices [1][2][3], optoelectronic devices [4,5], solar cells [6][7][8], energy storage devices [9,10], biosensors [11,12], chemical sensors [13,14], and field emission emitters [15,16]. To utilize the excellent properties of 1D nanostructures in the electronic devices, nanostructure welding technology, which can realize good Ohmic and machinal contact between an 1D nanostructure and an electrode, has been one of the most important processes in the application of 1D nanostructures.…”
Section: Introductionmentioning
confidence: 99%